THE USE OF DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILL - Devi Eka Ariyuni; Abdul Waris; Jamiluddin Jamiluddin (e-Journal of ELTS (English Language Teaching Society), 2021)
The objective of this research is to find out if applying Dictogloss technique can improve writing skills of eighth-grade students. The researcher applied pre-experimental research design. One hundred and thirty seven students of SMPN 5 Palu took part in this research, and class VIII A which consisted of 23 students were selected samples of the research. The data were collected using a test administered twice; it was in the form of a pre-test and a post-test. The data were analyzed statistically. The results of the data analysis showed that the t-counted value (15.3) was higher than that of the t-table (1.717) by applying a significance level of 0.05 with a degree of freedom (df) 22(n-1). This means that the hypothesis is accepted. In other words, applying Dictogloss technique can improve writing skills of eighth-grade students of SMPN 5 Palu.